Fiber treatment composition
A fiber treatment composition using zinc ricinoleate and specific solvents and compounds enhances deodorizing properties, addressing odor issues in repeated washing and body odor while maintaining transparency.
Patent Information
- Application Number
- JP2020110575
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-26
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2040-06-26
AI Technical Summary
Existing fiber treatment compositions using silicone, cationic surfactants, and cationic polymers for improving flexibility and smoothness in clothing suffer from odor accumulation due to repeated washing, especially with synthetic fiber blends, and lack effective deodorizing properties for body odor.
A fiber treatment composition incorporating fatty acid zinc salts like zinc ricinoleate, combined with specific solvents, polyoxyalkylene alkyl ethers, and amine compounds, to enhance solubility and maintain transparency, thereby improving deodorizing properties.
The composition effectively prevents odor accumulation from repeated washing and body odor, maintaining a highly transparent and uniform appearance.
Smart Images

Figure 0007601574000001 
Figure 0007601574000002 
Figure 0007601574000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a highly transparent fiber treatment composition. More specifically, the present invention relates to a highly transparent fiber treatment composition having excellent deodorizing properties. [Background technology]
[0002] As a fiber treatment agent, a silicone-based agent is known that is used in combination with a cationic surfactant or a cationic water-soluble polymer to improve the texture (softness and smoothness) of cotton or synthetic fiber clothing (Patent Documents 1 and 2). Some of these compositions contain a nonionic surfactant and one or more water-soluble solvents to make the appearance transparent (Patent Document 3). On the other hand, when the above composition is used for repeated washing, odorous components are also adsorbed to the fibers, causing odor to be generated and accumulated in the clothing. As a technology that is effective in suppressing odors in clothing, there is the addition of antibacterial compounds such as halogeno-o-hydroxydiphenyl compounds and antioxidants (Patent Documents 4 and 5). However, while this is capable of suppressing odors caused by bacteria, it has little effect on deodorizing odors that occur after repeated washing. In addition, there is a technology for imparting deodorizing properties to a liquid finishing composition for textile products that is based on a silicone compound and a cationic compound by blending a specific zinc compound (Patent Document 6). However, such a composition has low deodorizing properties for clothes that are repeatedly washed, particularly underwear made of synthetic fibers, and further low deodorizing properties for body odor of clothes after wearing. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2000-154476 A [Patent Document 2] JP 2009-155739 A [Patent Document 3] JP 2004-131895 A [Patent Document 4] JP 2005-187973 A [Patent Document 5] JP 2007-254902 A [Patent Document 6] JP 2009-57647 A Summary of the Invention [Problem to be solved by the invention]
[0004] Therefore, an object of the present invention is to provide a fiber treatment composition having excellent deodorizing properties and high transparency. [Means for solving the problem]
[0005] As a result of intensive research into the above-mentioned problems, it has been found that a fatty acid zinc salt such as zinc ricinoleate can impart high deodorizing properties to clothing. However, a fatty acid zinc salt such as zinc ricinoleate is a compound that is not soluble in water and is difficult to dissolve in commonly used solvents. In order to utilize such a fatty acid zinc salt such as zinc ricinoleate in a fiber treatment agent, it is desirable to dissolve it and make it uniform. Therefore, the present invention has been found by studying stabilization techniques necessary to maintain a highly transparent appearance in a composition containing a fatty acid zinc salt such as zinc ricinoleate.
[0006] The present invention relates to, for example, the following items [1] to [5]. [1] (A) zinc salt of a fatty acid having 8 to 22 carbon atoms, (B) one or more water-soluble solvents selected from the group consisting of monohydric alcohols having 1 to 4 carbon atoms, glycol ether solvents, and polyhydric alcohols having 2 to 6 carbon atoms and 2 to 6 hydroxyl groups, and (C) a polyoxyalkylene alkyl ether represented by the following formula (1) or (2): R a -O-(C2H4O) r -H (1) (In the formula, R a represents an alkyl or alkenyl group having 10 to 18 carbon atoms, and r is the average number of moles added, which is 2 to 30. R b -O-(C2H4O) s (C3H6O) t -H (2) (In the formula, R b represents an alkyl or alkenyl group having 10 to 18 carbon atoms, s and t each represent the average number of moles added, s is 2 to 30, and t is 1 to 20. and a ratio of the total amount of components (B) and (C) to component (A) is 25 or more. [2] (D) The fiber treatment composition according to the above [1], further comprising an amine compound represented by the following formula (3): R1(R2)N-(CH2) m -N(R3)R4(3) (In the formula, R1 to R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms which may have a hydroxyl group or an amino group, and m is an integer ranging from 2 to 6.) [3] (A) zinc salt of a fatty acid having 8 to 22 carbon atoms, (B) One or more water-soluble solvents selected from the group consisting of monohydric alcohols having 1 to 4 carbon atoms, glycol ether solvents, and polyhydric alcohols having 2 to 6 carbon atoms and 2 to 6 hydroxyl groups. (C) a polyoxyalkylene alkyl ether represented by the following formula (1) or (2): R a -O-(C2H4O) r -H (1) (In the formula, R a represents an alkyl or alkenyl group having 10 to 18 carbon atoms, and r is the average number of moles added, which is 2 to 30. R b -O-(C2H4O) s (C3H6O) t -H (2) (In the formula, R b represents an alkyl or alkenyl group having 10 to 18 carbon atoms, s and t each represent the average number of moles added, s is 2 to 30, and t is 1 to 20. and (D) an amine compound represented by the following formula (3): R1(R2)N-(CH2) m -N(R3)R4(3) (In the formula, R1 to R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms which may have a hydroxyl group or an amino group, and m is an integer ranging from 2 to 6.) and the ratio of the total amount of components (B) and (C) to the amount of component (A) is 5 or more. [4] The fiber treatment composition according to any one of the above [1] to [3], wherein the component (A) is zinc ricinoleate. [5] The fiber treatment composition according to any one of the above [1] to [4], further comprising (E) a silicone compound. Effect of the Invention
[0007] According to one aspect of the present invention, a fiber treatment composition having excellent deodorizing properties and high transparency can be provided. In this specification, transparency is evaluated based on whether or not the composition has a uniform appearance and the degree of turbidity. For example, if the composition has a uniform appearance, it can be determined that the composition has high transparency even if it is slightly turbid. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] [Component (A)] By incorporating component (A) in the fiber treatment composition of the present invention, it is possible to eliminate odors that build up with repeated washing and odors that adhere to clothing when worn. The component (A) is a zinc salt of a fatty acid having 8 to 22 carbon atoms, and examples thereof include zinc behenate, zinc caprate, zinc stearate, zinc ricinoleate, etc. Among these, zinc ricinoleate is preferred in terms of its adsorption to clothing and / or the stability of the salt with zinc. In the fiber treatment composition of the present invention, the component (A) may be used alone or in combination of two or more kinds. The amount of component (A) to be blended is not particularly limited as long as the blending purpose can be achieved, but is preferably 0.01 mass % or more, more preferably 0.1 mass % or more, and even more preferably 0.5 mass % or more, based on the total mass of the fiber treatment composition.
[0009] [(B) Component] By incorporating component (B) in the fiber treatment composition of the present invention, component (A) can be present in a finely divided state in the solvent. Component (B) is one or more water-soluble solvents selected from the group consisting of monohydric alcohols having 1 to 4 carbon atoms, glycol ether solvents, and polyhydric alcohols having 2 to 6 carbon atoms and 2 to 6 hydroxyl groups. Specific examples include ethanol, isopropanol, glycerin, butyl alcohol, ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, hexylene glycol, 1,3-butylene glycol, and diethylene glycol monobutyl ether. Among these, from the viewpoints of economy and safety to the human body and the environment, preferred examples include ethanol, glycerin, propylene glycol, 1,3-butylene glycol, diethylene glycol monobutyl ether, and the like. In the fiber treatment composition of the present invention, the component (B) may be used alone or in combination of two or more kinds. The amount of the (B) component is not particularly limited as long as it is an amount that can achieve the purpose of the blending, but is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 15% by mass or more, based on the total mass of the fiber treatment composition. In addition, the mass ratio B / A of the (B) component to the (A) component is preferably 15 or more, and more preferably 30 or more.
[0010] In the fiber treatment composition of the present invention, when a polyether-modified silicone is used as component (E) described below, component (B) is preferably ethanol, diethylene glycol monobutyl ether, or a combination thereof, which can also be finely emulsified with respect to component (E). The mass ratio B / E of the component (B) to the component (E) is preferably 0.3 or more. By mixing the components (B) and (E) in amounts such that the mass ratio B / E is 0.3 or more, the component (E) can be made sufficiently fine. Even if a large amount of the component (B) is used, the concentration of the component (E) becomes low, which is not economical, so the mass ratio B / E is preferably 10 or less, more preferably 5 or less.
[0011] [(C) component] By incorporating component (C) in the fiber treatment composition of the present invention, the solubility of component (A) can be improved. The component (C) is a polyoxyalkylene alkyl ether represented by the following formula (1) or (2). R a -O-(C2H4O) r -H (1) (In the formula, R a represents an alkyl or alkenyl group having 10 to 18 carbon atoms, and r is the average number of moles added, which is 2 to 30. R b -O-(C2H4O) s (C3H6O) t -H (2) (In the formula, R b represents an alkyl or alkenyl group having 10 to 18 carbon atoms, s and t each represent the average number of moles added, s is 2 to 30, and t is 1 to 20. In formula (1), R a R is preferably an alkyl group or an alkenyl group having 12 to 18 carbon atoms, and more preferably an alkyl group or an alkenyl group having 12 to 16 carbon atoms. a The alkyl or alkenyl group in may be linear or branched. In the formula (1), r is preferably 3-20, and more preferably 3-15. In formula (2), R b R is preferably an alkyl group or an alkenyl group having 12 to 18 carbon atoms, and more preferably an alkyl group or an alkenyl group having 12 to 16 carbon atoms. bThe alkyl or alkenyl group in may be linear or branched. In the formula (2), s is preferably 3-20, and more preferably 3-15. In the formula (2), t is preferably 1-10, and more preferably 1-5. In formula (2), (C2H4O) and (C3H6O) may be a random adduct or a block adduct. In the fiber treatment composition of the present invention, the component (C) may be used alone or in combination of two or more kinds.
[0012] The amount of component (C) is not particularly limited as long as it is an amount that can achieve the purpose of the blending, but is preferably 5 to 50 mass %, more preferably 5 to 40 mass %, and even more preferably 5 to 30 mass %, based on the total mass of the fiber treatment composition. In addition, the mass ratio C / A of component (C) to component (A) is preferably 15 or more. Furthermore, in order to improve the dispersion and / or solubility of component (A), in the fiber treatment composition of the present invention, the ratio of the total amount of components (B) and (C) to component (A) is preferably not less than 25, and more preferably not less than 30. However, when the fiber treatment composition of the present invention contains component (D) described below, the ratio of the total amount of components (B) and (C) to component (A) may be 5 or more.
[0013] [(D) component] In the fiber treatment composition of the present invention, an amine compound represented by the following formula (3) may be blended as component (D). By blending component (D) in the fiber treatment composition of the present invention, the solubility of component (A) can be improved. In addition, by blending component (D), higher transparency can be imparted to the fiber treatment composition of the present invention. R1(R2)N-(CH2) m -N(R3)R4(3) (In the formula, R1 to R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms which may have a hydroxyl group or an amino group, and m is an integer ranging from 2 to 6.) The number of hydroxyl groups or amino groups in each of R1 to R4 may be one or more, but is preferably one. The hydrocarbon groups of R1 to R4 may be linear or branched. R1 to R4 may each independently be, for example, a methyl group, an ethyl group, a propyl group, a butyl group, an isopropyl group, an isobutyl group, a sec-butyl group, a tert-butyl group, a hydroxymethyl group, a 2-hydroxyethyl group, a 3-hydroxypropyl group, a 2-hydroxypropyl group, a 4-hydroxybutyl group, a 3-hydroxybutyl group, a 2-hydroxybutyl group, a 2-methyl-3-hydroxypropyl group, a 2-methyl-2-hydroxypropyl group, a 1,1-dimethyl-2-hydroxyethyl group, an aminomethyl group, a 2-aminoethyl group, a 3-aminopropyl group, a 2-aminopropyl group, a 4-aminobutyl group, a 3-aminobutyl group, a 2-aminobutyl group, a 2-methyl-3-aminopropyl group, a 2-methyl-2-aminopropyl group, or a 1,1-dimethyl-2-aminoethyl group.
[0014] The component (D) is preferably N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine, N,N,N'-trimethyl-2-hydroxyethylethylenediamine, N,N,N'-triethyl-2-hydroxyethylethylenediamine, N,N,N'-trimethyl-3-hydroxypropylethylenediamine, N,N,N'-trimethyl-2-hydroxypropylethylenediamine, N,N-diethyl-N'-methyl-2-hydroxyethylethylenediamine, N,N,N'-trimethyl -2-hydroxyethylpropylenediamine, N,N,N'-trimethyl-2-hydroxyethylbutylenediamine, N,N-dimethyl-N',N'-bis(2-hydroxyethyl)ethylenediamine, N,N-diethyl-N',N'-bis(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N',N'-bis(3-hydroxypropyl)ethylenediamine, N,N-dimethyl-N',N'-bis(2-hydroxypropyl)ethylenediamine, N,N-dimethyl-N',N'-bis(3- N,N-dimethyl-N',N'-bis(2-hydroxypropyl)propylenediamine, N,N-diethyl-N',N'-bis(2-hydroxypropyl)ethylenediamine, N,N-diethyl-N',N'-bis(2-hydroxypropyl)propylenediamine, N,N,N'-trimethyl-2-aminoethylethylenediamine, N,N,N'-triethyl-2-aminoethylethylenediamine, N,N,N'-trimethyl-3-aminopropylethylenediamine The compound is at least one compound selected from the group consisting of N,N,N'-trimethyl-2-aminopropylethylenediamine, N,N-diethyl-N'-methyl-2-aminoethylethylenediamine, N,N,N'-trimethyl-2-aminoethylpropylenediamine, N,N,N'-trimethyl-2-aminoethylbutylenediamine, N,N-dimethyl-N',N'-bis(2-aminoethyl)ethylenediamine, and N,N-diethyl-N',N'-bis(2-aminoethyl)ethylenediamine. The amount of component (D) is not particularly limited as long as it is an amount that can achieve the purpose of the blending, but is preferably 0.01 to 5 mass %, more preferably 0.1 to 2 mass %, relative to the total mass of the fiber treatment composition. When the amount of component (D) is within the range of 0.01 to 5 mass %, it not only takes in and solubilizes component (A) to impart a highly transparent appearance to the fiber treatment composition, but also allows component (A) to be uniformly adsorbed onto clothing.
[0015] [(E) component] In the fiber treatment composition of the present invention, a silicone compound generally used in treating fiber products may be blended as component (E). The silicone compound is not particularly limited as long as it can impart smoothness to the fiber product when adsorbed thereon. Silicone compounds commonly used in textile treatments include dimethyl silicone, polyether-modified silicone, methylphenyl silicone, alkyl-modified silicone, higher fatty acid-modified silicone, methylhydrogen silicone, fluorine-modified silicone, epoxy-modified silicone, epoxy polyether-modified silicone, carboxy-modified silicone, polyglycerol-modified silicone, carbinol-modified silicone, amino-modified silicone, aminopolyether-modified silicone, polyether-long-chain alkyl-aralkyl-modified silicone, and the like. These can be used alone or in combination of two or more. The molecular structure of the silicone compound may be linear, branched, or crosslinked. The modified silicone compound may be modified with one type of organic functional group, or may be modified with two or more types of organic functional groups. The kinetic viscosity of silicone compounds at 25°C is 10 to 100,000,000 mm 2 / s, and 1,000 to 100,000 mm 2 A kinematic viscosity in this range is preferable in terms of ease of blending and the slipperiness of the fabric treated with the composition of the present invention.
[0016] The silicone compound may be used as an oil. From the viewpoint of high adsorption effect to fibers and enhancement of softness and smoothness, the silicone compound is preferably nonionic, and more preferred examples include dimethyl silicone, carbinol-modified silicone, polyglycerol-modified silicone, epoxy-modified silicone, polyether-modified silicone, amino-modified silicone, and aminopolyether-modified silicone. Among these, particularly preferred silicone compounds include polyether-modified silicone, aminopolyether-modified silicone, and dimethyl silicone from the viewpoint of imparting softness and preventing discoloration and appearance. These silicone compounds have less squeaky feeling and good softness compared to low molecular weight dimethyl silicone without polyether group. A preferred polyether-modified silicone is a copolymer of alkyl (carbon number 1-3) siloxane and polyoxyalkylene (alkylene group preferably has carbon number 2-5). Among these, a copolymer of dimethylsiloxane and polyoxyalkylene (polyoxyethylene, polyoxypropylene, random or block copolymer of polyoxyethylene and polyoxypropylene, etc.) is preferred. Examples of such a copolymer include compounds represented by the following general formula (I) or (II).
[0017] [ka] (In the formula, M, N, a, and b are average degrees of polymerization, and R represents hydrogen or an alkyl group.) Here, M is 10 to 10,000, preferably 100 to 300, N is 1 to 1,000, preferably 1 to 100, and it is preferable that M>N, a is 2 to 100, preferably 2 to 50, and b is 0 to 50, preferably 0 to 10. R is preferably hydrogen or an alkyl group having 1 to 4 carbon atoms. The polyether-modified silicone represented by general formula (I) can generally be produced by addition reaction of an organohydrogenpolysiloxane having a Si-H group with a polyoxyalkylene alkyl ether having a carbon-carbon double bond at the end, such as polyoxyalkylene allyl ether, in the presence of a platinum catalyst.Therefore, the polyether-modified silicone may contain a small amount of unreacted polyoxyalkylene alkyl ether or organohydrogenpolysiloxane having a Si-H group.Since the organohydrogenpolysiloxane having a Si-H group is highly reactive, it is preferable that the amount present in the polyether-modified silicone is 30 ppm or less (as the amount of -H).
[0018] [ka] (In the formula, A, B, h, and i are average degrees of polymerization, R represents an alkyl group, and R' represents hydrogen or an alkyl group.) Here, A is preferably 5 to 10,000, B is preferably 2 to 10,000, h is preferably 2 to 100, and i is preferably 0 to 50. R is preferably an alkyl group having 1 to 5 carbon atoms. R' is preferably hydrogen or an alkyl group having 1 to 4 carbon atoms. From the viewpoint of imparting flexibility and smoothness, the weight average molecular weight of the block copolymer represented by formula (II) is preferably 15,000 to 100,000,000. The linear polysiloxane-polyoxyalkylene block copolymer represented by the above formula (II) can be produced by reacting a polyoxyalkylene compound having a reactive terminal group with a dihydrocarbylsiloxane having a terminal group that reacts with the reactive terminal group of the polyoxyalkylene compound.
[0019] A specific example of polyether modified silicone oil is DOWSIL TMseries (including those in the catalog of the former Dow Corning Toray Co., Ltd.), FZ-2164, FZ-2154, FZ-2191, L-7001, FZ-2120, L-7002, SH3749, SH3771, SH3772, SH3775, CF1188N, SF8410, FZ-2104, FZ-7604, FZ-2161, FZ-2222, KF352A, KF6008, KF615A, KF6016, KF6017 manufactured by Shin-Etsu Chemical Co., Ltd., and TSF4450 and TSF4452 manufactured by Momentive Japan. Specific examples of aminopolyether modified silicone oils include DOWSIL 1000 series manufactured by Dow Toray Co., Ltd. TM These may be used alone or in combination of two or more. The amount of the silicone compound is not particularly limited, but from the viewpoints of smoothness and viscosity of the composition, it is preferably 0.1 to 50% by mass, more preferably 3 to 50% by mass, and particularly preferably 6 to 15% by mass, based on the total mass of the fiber treatment composition. This makes it possible to provide excellent effects such as smoothness and to provide good uniform adsorption.
[0020] [Component (F)] The fiber treatment composition of the present invention may contain a cationic water-soluble polymeric compound as component (F). Such a water-soluble polymeric compound has the effect of adsorbing the silicone compound to the fiber. As the cationic water-soluble polymeric compound, those that have cationic properties when dissolved in water can be used, but as the cationic water-soluble polymeric compound, in particular, a water-soluble polymeric compound having one or more cationic groups selected from amino groups, amine groups, and quaternary ammonium groups is preferred. In this specification, the water-soluble polymer refers to a polymeric compound that is transparent and not cloudy when 1 g of the polymeric compound is added to 100 g of water at 25°C. The cationic water-soluble polymeric compound preferably has a cationic degree of 0.1% or more, for example, 0.1 to 35%, and particularly preferably 2.5% or more, for example, 2.5 to 15%. If the cationic degree satisfies such conditions, the effect of adsorbing the coexisting silicone compound to the fiber can be excellent, and the case where a large amount of the compound is required and is not economical can be prevented. Here, the degree of cationization is defined as a value calculated by the following formula (A) when the polymer compound is a polymer of a cationic monomer, a copolymer of a cationic monomer and a nonionic monomer, or a nonionic polymer partially modified or substituted with a cationic group (such as cationic cellulose), or by the following formula (B) when the polymer compound is a copolymer of a cationic monomer and an anionic monomer, or a copolymer of a cationic monomer, an anionic monomer, and a nonionic monomer.
[0021] Cationization degree (%) = X × Y × 100 Formula (A) [X: Atomic weight of the cationized atom (nitrogen, etc.) in the cationic group of the polymer compound Y: number of moles of cationic groups contained in 1 g of polymer compound] Cationization degree (%) = X × (YZ) × 100 Formula (B) [X: Atomic weight of the cationized atom (nitrogen, etc.) in the cationic group of the polymer compound Y: The number of moles of cationic groups contained in 1 g of polymer compound Z: the number of moles of anionic groups contained in 1 g of polymer compound (the anionic groups of Z include carboxyl groups and sulfonic acid groups contained in monomer units in the polymer chain. Specifically, they are carboxylic acids in acrylic acid. However, they do not include counter ions of cationic groups.) As an example of calculating the degree of cationization, the case of MERQUAT280 (manufactured by NALCO) represented by the following formula (III) will be shown.
[0022] [ka] Mass ratio of dimethyldiallylammonium chloride to acrylic acid = 80:20 X: 14 (atomic weight of nitrogen atom) Y: 4.95×10 -3 (Calculated from the weight of cationic groups per 1 g: 0.8 g and the molecular weight of the cationic groups) Z:2.78×10 -3 (Weight of anionic group per 1 g: 0.2 g, calculated from the molecular weight of the anionic group) From equation (2), Cationization degree (%) = 14 × (4.95 × 10 -3 -2.78×10 -3 )×100=3.0.
[0023] Therefore, according to the above-described method for calculating the degree of cationization, the degree of cationization of a polymer of a nonionic monomer or a polymer of an anionic monomer is 0%. The cationic water-soluble polymer preferably has a weight-average molecular weight of 1,000 to 5,000,000, more preferably 3,000 to 1,000,000, and even more preferably 5,000 to 500,000, as measured by gel permeation chromatography using polyethylene glycol as a standard substance. This makes it possible to suppress an increase in viscosity and ensure excellent usability. Specific examples of water-soluble polymer compounds having cationic properties include polymers of dimethyldiallylammonium chloride such as Merquat 100 (manufactured by Lubrizol), Adeka Catioace PD-50 (manufactured by Asahi Denka Kogyo Co., Ltd.), Daidol EC-004, and Daidol EC-315D (manufactured by Daido Kasei Kogyo Co., Ltd.), copolymers of dimethyldiallylammonium chloride and acrylamide such as Merquat 550 (manufactured by Lubrizol), copolymers of dimethyldiallylammonium chloride and acrylic acid such as Merquat 280 (manufactured by Lubrizol), and Leoguard MGP and Leoguard KGP (manufactured by Lion Corporation). Examples of such a polymer include cationic cellulose such as LUVIQUAT-FC905 (manufactured by BASF), imidazolinium chloride-vinylpyrrolidone copolymer such as LUVIQUAT-FC905 (manufactured by BASF), polyethyleneimine such as LUGALVAN-G15000 (manufactured by BASF), cationic polyvinyl alcohol such as Poval 11-98 (manufactured by Kuraray Co., Ltd.), natural polymer derivatives having an amino group such as chitosan, and copolymers of vinyl monomers having a hydrophilic group to which diethylamino methacrylate-ethylene oxide or the like is added. However, the polymer compound may be any polymer compound that has cationic properties when dissolved in water, and is not limited to these examples. Among these, from the viewpoint of not interfering with the feel such as flexibility imparted by the silicone, those which impart small stiffness to the fiber when the cationic polymer is adsorbed alone are preferred. A particularly preferred polymer is a cationic polymer obtained by polymerizing dimethyldiallylammonium salt. The cationic water-soluble polymer compound may be used alone or in combination. The amount of the cationic water-soluble polymer compound is not particularly limited, but is preferably within a range that does not impart rigidity to the textile product, for example, 0.1-30% by mass, more preferably 0.5-10% by mass, based on the total mass of the fiber treatment composition. By using this range, it is possible to enhance the silicone adsorption promotion effect, to provide sufficient effects such as softness and smoothness, and to suppress the increase in viscosity, making the product easy to use.
[0024] [Other optional ingredients] <Fragrance> The fiber treatment composition of the present invention may contain a perfume to make the composition smell. Lists of perfume raw materials that can be used can be found in various documents, such as "Perfume and Flavor Chemicals", Vol. I and II, Steffen Arctander, Allured Pub. Co. (1994); "Synthetic perfumes: Chemistry and product knowledge", Genichi Indo, Chemical Industry Daily Co. (1996); "Perfume and Flavor Materials of Natural Origin", Steffen Arctander, Allured Pub. Co. (1994); "Encyclopedia of fragrances", edited by the Japan Fragrance Association, Asakura Shoten (1989); "Perfumery Material Performance V.3.3", Boelens Aroma Chemical Information Service (1996); and "Flower oils and Floral Compounds In Perfumery", Danute Lajaujis Anonis, Allured Pub. Co. (1993), each of which is incorporated herein by reference.
[0025] <Dye and / or pigment> Dyes and pigments, respectively, may be included to improve the appearance of the fabric treatment composition. Both the dyes and pigments can be used without any particular restrictions, and are known in the field of fiber treatment agents. Specific examples of dyes that can be added are described in Dyes Handbook (edited by the Organic Synthesis Chemistry Association, published July 20, 1970, Maruzen Co., Ltd.) and the like. In addition, dyes described in JP-A-6-123081, JP-A-6-123082, JP-A-7-18573, JP-A-8-27669, JP-A-9-250085, JP-A-10-77576, JP-A-11-43865, JP-A-2001-181972, JP-A-2001-348784, and the like can also be used. Preferably, the dye is at least one water-soluble dye of red, blue, yellow or purple selected from acid dyes, direct dyes, basic dyes, reactive dyes, and mordant / acid mordant dyes. The dye and the pigment may each be used alone or in combination of two or more kinds. The amount of each of the dye and pigment to be added is not particularly limited as long as the purpose of the addition can be achieved, but is preferably 1 to 50 ppm, more preferably 1 to 30 ppm, based on the total mass of the fiber treatment composition.
[0026] <Preservatives> The preservative may be added mainly to enhance the preservative or bactericidal power of the fiber treatment composition and to maintain the preservative properties during long-term storage. As the preservative, any component known in the field of fiber treatment agents can be used without particular limitation, specific examples of which include isothiazolone-based organic sulfur compounds, benzisothiazolone-based organic sulfur compounds, benzoic acids, phenol-based phenol compounds, and 2-bromo-2-nitro-1,3-propanediol. Examples of isothiazolone organic sulfur compounds include 5-chloro-2-methyl-4-isothiazolin-3-one, 2-n-butyl-3-isothiazolone, 2-benzyl-3-isothiazolone, 2-phenyl-3-isothiazolone, 2-methyl-4,5-dichloroisothiazolone, 5-chloro-2-methyl-3-isothiazolone, 2-methyl-4-isothiazolin-3-one, and mixtures thereof. Of these, 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one are preferred, and a mixture of 5-chloro-2-methyl-4-isothiazolin-3-one and 2-methyl-4-isothiazolin-3-one is more preferred, with a mixture of about 77% by mass of the former and about 23% by mass of the latter and a diluted solution thereof (e.g., isothiazolone solution) being particularly preferred, and a specific example is Caisson CG-ICP manufactured by DDP Specialty Products Japan, Ltd. Examples of benzisothiazolone-based organic sulfur compounds include 1,2-benzisothiazolin-3-one, 2-methyl-4,5-trimethylene-4-isothiazolin-3-one, and related compounds such as dithio-2,2-bis(benzmethylamide), and mixtures thereof. Among these, 1,2-benzisothiazolin-3-one is particularly preferred, and specific examples include Nippacide manufactured by Clariant Co., Ltd., and Proxel BDN, Proxel GXL, Proxel XL, Proxel LV, Proxel CRL, Proxel NBZ, Proxel AM, and Proxel B20 manufactured by Lonza Co., Ltd. Examples of benzoic acids and phenol compounds that can be used include benzoic acid or a salt thereof, salicylic acid or a salt thereof, parahydroxybenzoic acid or a salt thereof, methyl paraoxybenzoate, ethyl paraoxybenzoate, propyl paraoxybenzoate, butyl paraoxybenzoate, benzyl paraoxybenzoate, 3-methyl-3-isopropylphenol, o-phenylphenol, 2-isopropyl-5-methylphenol, resorcin, cresol, and 2,6-di-tert-butyl-p-cresol. The content of the preservative is not particularly limited as long as the purpose of the blending can be achieved, but is preferably 0.0001 to 1 mass% based on the total mass of the fiber treatment composition. If the content is 0.0001 mass% or more, the blending effect of the preservative can be sufficiently obtained, and if it is 1 mass% or less, the high storage stability of the fiber treatment composition can be sufficiently maintained.
[0027] <Antibacterial agent> The antibacterial agent can impart an antibacterial effect to clothing when fibers are treated with the fiber treatment composition, and can be blended to improve the storage stability of the composition. As the antibacterial agent, any component known in the field of fiber treatment agents can be used without particular limitation. Specific examples include alkyltrimethylammonium salts having 12 to 16 carbon atoms (Lipocard C12-37W, Lipocard C50, Lipocard C16Cl salt, Lipocard C16MS salt, etc., manufactured by Lion Specialty Chemicals), dialkyldimethylammonium salts (Lipocard 210-80E, manufactured by Lion Specialty Chemicals, Carboquat MW50, etc., manufactured by Lonza), dialkylmethylpolyammonium propionate (Bardap 26, manufactured by Lonza), diclosan (Tinosan HP100, manufactured by BASF, etc.), triclosan, benzalkonium chloride (Barquat MS100, Barquat MB80, etc., manufactured by Lonza), benzethonium chloride, bis-(2-pyridylthio-1-oxide)zinc, 8-oxyquinoline, biguanide compounds (Proxel IB, manufactured by Lonza), chlorohexidine hydrochloride, and polylysine. Among these, C12-16 alkyltrimethylammonium salts, benzalkonium chloride, biguanide compounds, and chlorohexidine hydrochloride are preferred. The content of the antibacterial agent is not particularly limited as long as the purpose of the blending can be achieved, but it is preferably 0.001 to 5% by mass based on the total mass of the fiber treatment composition.
[0028] <Ultraviolet absorbing agent> An ultraviolet absorber may be incorporated in the fiber treatment composition to protect the composition from ultraviolet rays. UV absorbers are components that absorb UV rays, convert them into infrared rays or visible light, etc., and release them to provide UV protection. As the ultraviolet absorbing agent, any component known in the field of liquid fabric softeners can be used without particular limitation. Specific examples include aminobenzoic acid derivatives such as p-aminobenzoic acid, ethyl p-aminobenzoate, glyceryl p-aminobenzoate, and amyl p-dimethylaminobenzoate; salicylic acid derivatives such as ethylene glycol salicylate, dipropylene glycol salicylate, octyl salicylate, and myristyl salicylate; cinnamic acid derivatives such as methyl diisopropylcinnamate, ethyl p-methoxycinnamate, isopropyl p-methoxycinnamate, 2-ethylhexyl p-methoxycinnamate, and butyl p-methoxycinnamate; benzophenone derivatives such as 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxybenzophenone-5-sulfonic acid, and 2,2'-dihydroxy-4-methoxybenzophenone; azole compounds such as urocanic acid and ethyl urocanate; and 4-t-butyl-4'-methoxybenzoylmethane. The content of the ultraviolet absorbing agent is not particularly limited as long as the purpose of the blending can be achieved, but it is preferably 0.001 to 5% by mass based on the total mass of the fiber treatment composition.
[0029] <Antifoaming agent> When a defoaming agent is blended into the fiber treatment composition of the present invention, foaming during fiber treatment and foaming during measuring the composition can be suppressed. Examples of defoaming agents include silicone-based defoaming agents, alcohol-based defoaming agents, ester-based defoaming agents, mineral oil-based defoaming agents, vegetable oil-based defoaming agents, and synthetic oil-based defoaming agents, with silicone-based defoaming agents being preferred. Examples of silicone-based defoaming agents include oil-based defoaming agents, compound-based defoaming agents, self-emulsifying defoaming agents, emulsion-based defoaming agents, powder-based defoaming agents, and solid-based defoaming agents, with self-emulsifying defoaming agents and emulsion-based defoaming agents being preferred. The blending amount of the defoaming agent is not particularly limited, but can be 0.1 ppm to 1.0 mass % based on the total mass of the composition, and more preferably 1 ppm to 0.05 mass %.
[0030] <Other> In addition to the above-mentioned optional components, additives used in ordinary fiber treatment agents can be used within the scope of not impairing the effects of the present invention. Specific examples of such additives include cationic surfactants, oils such as liquid paraffin and higher alcohols, urea, hydrocarbons, nonionic cellulose derivatives, ultraviolet absorbers, fluorescent whitening agents, etc., which can be appropriately blended. In addition, antioxidants and reducing agents for improving the stability of the fragrance and color tone of the fiber treatment agent composition, opacifiers (polystyrene emulsions, etc.), opacifying agents, shrink prevention agents, washing wrinkle prevention agents, shape retention agents, drape retention agents, ironing improvers, oxygen bleaching inhibitors, whitening agents, whitening agents, fabric softening clays, antistatic agents, dye transfer inhibitors (polyvinylpyrrolidone, etc.), polymer dispersants, dirt release agents, scum dispersants, fluorescent whitening agents (4,4-bis(2-sulfostyryl)biphenyl disodium, etc.), dye fixatives, anti-fading agents (1,4-bis(3-aminopropanediol), etc.), and other additives can be appropriately blended. In addition, the following may be appropriately blended: an enzyme such as propyl piperazine, a stain remover, a fiber surface modifier (enzymes such as cellulase, amylase, protease, lipase, and keratinase), a foam inhibitor, and a component that imparts the texture and function of silk, such as moisture absorption and release properties (silk protein powder, surface modified products thereof, and emulsified dispersions, specifically K-50, K-30, K-10, A-705, S-702, L-710, FP series (Idemitsu Petrochemicals), hydrolyzed silk liquid (Jomo), and Silkgen G Soluble S (Ichimaru Falcos)); a stain prevention agent (a nonionic polymer compound consisting of an alkylene terephthalate and / or alkylene isophthalate unit and a polyoxyalkylene unit, such as FR627 manufactured by GOO Chemical Industry Co., Ltd. and SRC-1 manufactured by Clariant), and a pH adjuster described below. When an anionic surfactant or an anionic polymer compound is added, it is advisable to add it in an amount lower than the content of the cationic polymer compound of component (F), taking into consideration the adsorption effect of the silicone compound. When an antioxidant is added, from the viewpoint of the appearance and storage stability of the fiber treatment composition, preferred are BHT (butyl hydroxytoluene), methoxyphenol, tocopherol compounds, etc. The antioxidant is preferably used in an amount of 0.01 to 1.0 mass%.
[0031] <Water> The fiber treatment composition is preferably a liquid aqueous composition containing water. As the water, any of tap water, ion-exchanged water, pure water, distilled water, etc. can be used, with ion-exchanged water being preferred.
[0032] [pH of composition] The pH (measured at 25° C. using a glass electrode) of the fiber treatment composition of the present invention is not particularly limited, but is preferably in the range of 4 to 8, and more preferably in the range of 5 to 7. In order to adjust the pH to within this range, a pH adjuster such as a short-chain amine compound such as hydrochloric acid, sulfuric acid, phosphoric acid, alkyl sulfuric acid, benzoic acid, paratoluenesulfonic acid, citric acid, malic acid, succinic acid, lactic acid, glycolic acid, hydroxyethanediphosphonic acid, phytic acid, ethylenediaminetetraacetic acid, triethanolamine, diethanolamine, dimethylamine, N-methylethanolamine, or N-methyldiethanolamine, an alkali metal hydroxide such as sodium hydroxide, an alkali metal carbonate, or an alkali metal silicate can be used as necessary.
[0033] [Viscosity of composition] The viscosity of the fiber treatment composition of the present invention (at 25°C, using a Brookfield viscometer with a No. 2 rotor, reading after 10 revolutions) is not particularly limited, but in the case of a product to be added to rinse water in the rinsing step of laundry, it is preferably 500 mPa s or less, while in the case of a product filled in a trigger spray container, dispenser container, etc. and sprayed directly onto fiber products, a viscosity of 100 mPa s provides good usability.
[0034] [Method of preparing the composition] The method for preparing the fiber treatment composition of the present invention is not particularly limited, and the fiber treatment composition of the present invention can be prepared by mixing each component. For example, the (A) component and the (B) component are placed in a container such as a glass beaker and stirred, and then the (C) component is added while stirring. The (D) component and other optional components are not particularly limited, and may be added after the (C) component is added.
[0035] [Method of using the composition] The application and method of use of the fiber treatment composition of the present invention are not particularly limited, but when used on natural fiber products such as cotton or chemical fiber products such as polyester, the composition may be placed in the detergent or fabric softener inlet of a washing machine to treat clothes in the washing machine, or may be placed in a trigger spray container to spray on clothes. In either case, as long as component (A) adheres or adsorbs at 0.001% or more by weight of the fabric, high deodorizing performance can be imparted to any fabric. EXAMPLES
[0036] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the examples, the amounts of components are all expressed in mass% (based on pure content unless otherwise specified).
[0037] [Component (A)] A-1: Zinc ricinoleate (TEGOSORB Conc50, EVONIK) A-2: Zinc stearate (reagent, Fujifilm Wako Pure Chemical Industries, Ltd.) A-3 (Comparative Example): Zinc gluconate (reagent, Fujifilm Wako Pure Chemical Industries, Ltd.)
[0038] [(B) Component] B-1: 95% ethanol (reagent, from Japan Alcohol Sales) B-2: Butyl carbitol (reagent, Tokyo Chemical Industry Co., Ltd.)
[0039] [(C) component] C-1: Polyoxyethylene alkyl ether (C12-14, EO10) (EMALEX710, Nippon Emulsion) C-2 (Comparative Example): Polyoxyethylene alkyl ether (C13, EO40) (Leocol TDA-400-75, Lion Specialty Chemicals)
[0040] [(D) component] D-1: N,N,N',N'-tetrakis(2-hydroxypropyl)ethylenediamine (reagent, Tokyo Chemical Industry Co., Ltd.)
[0041] [(E) component] E-1: Polyether modified silicone (DOWSIL TM CF1188N, manufactured by Dow Toray Co., Ltd.) E-2: Polyether modified silicone (DOWSIL TM SH3775, manufactured by Dow Toray Co., Ltd.) E-3: Aminopolyether modified silicone (DOWSIL TM FZ-3789, manufactured by Dow Corning Toray Co., Ltd.)
[0042] [Component (F)] F-1: Polymers of dimethyldiallylammonium chloride. (MERQUAT TM 100, manufactured by Lubrizol)
[0043] [Other optional ingredients] G-1: A fragrance composition containing fragrance ingredients according to the composition shown in Table 1 below. [Table 1]
[0044] [Method of preparing fiber treatment composition] In a 100 mL glass beaker, component (A) was added, followed by component (B), and the mixture was stirred with a stirrer of about 3 cm. Next, component (C) was added while stirring the mixture of components (A) and (B), and then water was added while stirring the mixture after component (C) was added, and then component (D) was added. When components (E), (F), and (G) were added, they were added to the mixture before the addition of water and stirred. In all cases, an appropriate amount of sulfuric acid (reagent) was added to adjust the pH to 7, and finally the balance was made with water. The compositions of the prepared fiber treatment compositions are shown in Tables 2 and 3 below.
[0045] <Evaluation of odor of clothes after wearing (Evaluation 1)> The clothes to be washed were AIRism (UNIQLO: Fast Retailing Co., Ltd.) made of 90% polyester and 10% polyurethane, and the washing was carried out under the following conditions. In a Panasonic drum washing machine NA-VX700, Top NANOX was placed in the detergent inlet, the fiber treatment composition prepared according to the above preparation method was placed in the finishing agent inlet, and the washing was carried out on the automatic cycle (cloth weight: 1 kg). After washing, the dried clothes were worn for 8 hours a day, and the odor of the clothes after wearing was evaluated by 6 evaluators based on the following 6-stage odor intensity standard. The results are shown as the average of the 6 evaluators and are shown in the "Evaluation 1" section in Table 2 below. A score of less than 3 points was considered to be acceptable. (6-level odor intensity scale) 5 points: strong odor, 4 points: strong odor, 3 points: easily detectable odor, 2 points: weak odor, 1 point: not detectable odor, 0 point: no odor.
[0046] <Evaluation of odor accumulation due to repeated washing (Evaluation 2)> Airism (UNIQLO: Fast Retailing Co., Ltd.) made of 90% polyester and 10% polyurethane was worn during the day, and the clothes were repeatedly washed under the following conditions. In a Panasonic drum washing machine NA-VX700, Top NANOX was set in the detergent inlet, the fiber treatment composition prepared according to the above preparation method was set in the finishing agent inlet, and 10 pieces of wet artificially soiled cloth of 20 cm x 20 cm were washed 10 times on the automatic cycle (the total amount of cloth was 1 kg for the worn clothes and the artificially soiled cloth). The odor of the clothes after repeated washing was evaluated by six evaluators based on the following six-level odor intensity standard. The results are shown as the average of the six evaluators and are shown in the "Evaluation 2" section in Table 3 below. A score of less than 3 points was considered to be acceptable. The wet artificially soiled cloth was purchased from the Laundry Science Association. (6-level odor intensity scale) 5 points: strong odor, 4 points: strong odor, 3 points: easily detectable odor, 2 points: weak odor, 1 point: not detectable odor, 0 point: no odor.
[0047] [Method of evaluating fiber treatment composition] <Appearance evaluation (Evaluation 3)> The fiber treatment composition prepared according to the above preparation method was transferred to a transparent glass bottle with a sealable lid and allowed to stand at room temperature for 24 hours, and its appearance was evaluated according to the following criteria. △ or better was considered to be acceptable. The results are shown in the "Evaluation 3" section in Tables 2 and 3 below. ×: Precipitation △: Uniform appearance, but slightly cloudy 〇: Uniform appearance, mostly clear, but slightly cloudy ◎: Uniform appearance, clear
[0048] [Table 2] In the table, the numerical values for the composition of each component represent mass %.
[0049] [Table 3] In the table, the numerical values for the composition of each component represent mass %.
Claims
1. (A) a zinc salt of a fatty acid having 8 to 22 carbon atoms, (B) one or more water-soluble solvents selected from the group consisting of monohydric alcohols having 1 to 4 carbon atoms, glycol ether solvents, and polyhydric alcohols having 2 to 6 carbon atoms and 2 to 6 hydroxyl groups; (C) a polyoxyalkylene alkyl ether represented by the following formula (1) or (2): R a -O-(C 2 H 4 O) r -H (1) (In the formula, R a represents an alkyl or alkenyl group having 10 to 18 carbon atoms, and r is the average number of moles added, which is 2 to 30. R b -O-(C 2 H 4 O) s (C 3 H 6 O) t -H (2) (In the formula, R b represents an alkyl or alkenyl group having 10 to 18 carbon atoms, s and t each represent the average number of moles added, s is 2 to 30, and t is 1 to 20. and (D) an amine compound represented by the following formula (3): R 1 (R 2 )N-(CH 2 ) m -N(R 3 )R 4 (3) (In the formula, R 1 ~R 4 each independently represents a hydrocarbon group having 1 to 4 carbon atoms which may have a hydroxyl group or an amino group, and m is an integer ranging from 2 to 6. Contains The blending amount of (C) is 3 to 30 mass %, The blending amount of (D) is 0.1 to 5 mass %, and A fiber treatment composition, in which the ratio of the total amount of components (B) and (C) to component (A) is 5 or more.
2. 2. The fiber treatment composition according to claim 1, wherein component (A) is zinc ricinoleate.
3. The fiber treatment composition according to claim 1 or 2, further comprising (E) a silicone compound.
Citation Information
Patent Citations
Deodorising compsn. for cosmetic or household goods - contg. zinc salt of ricinoleic acid, ethoxylated long chain fatty alcohol and tert. amine
DE4014055A1
Cloth treatment composition
JP1988203866A
Aqueous finishing agent composition for fiber product
JP2000154476A
Preparation with deodorizing activity comprising zinc salt of ricinoleic acid and at least one functional amino acid
JP2003226630A
Composition for deodorization
JP2003230623A
